Exploring the Cultural Values of Naming La Ode and Wa Ode in Muna and Buton Communities of South East Sulawesi - Jalil, Abdul; Hasniah; Ashmarita (Tradition and Modernity of Humanity, 2021)
This theme was inspired by the RRI Kendari program at the event of networking culture organized by the Regional Office of Sulawesi on May 15, 2017. La Ode and Wa Ode were noble titles or at least considered the prayers from parents to their children so that their children would become leaders or nobles in the future. In addition, La Ode and Wa Ode were the acronyms of the two statements of the Islamic creed. The word "La" stands for La Ilaha Ilallah while the word "Wa" stems from Wa Asyahadu Anna Muhammad Darasulullah. This paper aims to explore cultural values in the naming of La Ode and Wa Ode in the communities of Muna and Buton. The method used was descriptive analytics through observation and interviews. This study found that La Ode and Wa Ode's naming has changed, although, at the same time, it has become a cultural heritage of the Indonesian archipelago. Furthermore, along with the development of globalization, La Ode and Wa Ode have experienced cultural degradation to some extent. Thus, the addition of La Ode and Wa Ode is not always attached to the title of nobility.